2011
DOI: 10.1143/jjap.50.036101
|View full text |Cite
|
Sign up to set email alerts
|

Lamb-Dip Laser-Induced Fluorescence Spectroscopy for Measuring Magnetic Field in a Plasma

Abstract: We have developed a Lamb-dip laser-induced fluorescence (LIF) system to precisely measure the local magnetic field strength in a plasma. Utilizing the hole burning effect, we made sharp dips on the LIF spectrum as the frequency markers and accurately determined the Zeeman splitting by reading the frequency interval of the dips. The method is valid even in the conditions where the Doppler broadening of the LIF spectrum is larger than the Zeeman shift. The newly developed LIF system is capable of determining a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Compared with the fluorescence signal observed using a single laser pass, the fluorescence signal intensity can be intensified using two laser beams. 18) A clear Lamb-dip was successfully observed by counterpropagating laser beams at the back of the sleeve. However, it must be noted that only the most abundant isotope, 88 Sr, was detectable by this Lamb-dip.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…Compared with the fluorescence signal observed using a single laser pass, the fluorescence signal intensity can be intensified using two laser beams. 18) A clear Lamb-dip was successfully observed by counterpropagating laser beams at the back of the sleeve. However, it must be noted that only the most abundant isotope, 88 Sr, was detectable by this Lamb-dip.…”
Section: Resultsmentioning
confidence: 96%
“…However, it must be noted that only the most abundant isotope, 88 Sr, was detectable by this Lamb-dip. The frequency profile of a fluorescence signal with one Lamb-dip is modeled by the equation below: 18) S A…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Velocity resolution of laser-induced fluorescence (LIF) spectroscopy 1 has been greatly improved by using diode lasers. [2][3][4][5][6][7][8][9][10] Precise measurement of velocity distribution function has become possible in the experiments. We have measured the velocity distribution function of neutrals in an electron cyclotron resonance (ECR) plasma, and examined the relationship between asymmetric distribution function and flow generated by inhomogeneity.…”
Section: Introductionmentioning
confidence: 99%
“…This structure is considered to be suitable for examining the relationship between asymmetry of distribution function and inhomogeneity-induced flow. A high resolution LIF method 9,10 has been used to measure the distribution functions with velocity component parallel and perpendicular to the neutral density gradient. It has been found that the asymmetry of distribution function is generated in the direction of density gradient of neutrals.…”
Section: Introductionmentioning
confidence: 99%